Systematic Literature Review (SLR): Application of Technology to the Education Curriculum in Islamic Religious Education Subjects in High Schools (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Technology plays a significant role in the education sector, particularly in influencing students' learning motivation. This study aims to evaluate the influence of technology-based curriculum implementation on students' learning motivation, specifically within Islamic Religious Education (PAI) subjects at the Senior High School level. This study utilizes a Systematic Literature Review (SLR) method with the PRISMA approach. A comprehensive search of databases (Google Scholar and Sinta) identified relevant articles published between 2020 and 2025. After a rigorous screening process, 15 articles were selected for in-depth analysis. The results indicate that the integration of technology manifested through learning applications (Quizizz), digital content creation tools (CapCut), and interactive platforms (YouTube, Tablets) significantly increases students' interest and participation in PAI learning activities. The study concludes that technology serves as a vital bridge in the modern PAI curriculum, transforming abstract religious concepts into engaging visual experiences. However, successful implementation requires careful management and teacher digital competence to ensure a positive and sustained impact on student motivation.